Productivity of Contemporary Economies Theory and Evidence - Filipenko, Anton S.; Moskalenko, Oleksandra M.; Zaitsev, Yurii K. (Cambridge Scholars Publisher, 2021)
This book reveals the results of original research into the productivity of economies from the theoretical and empirical points of view. Urgently, the current economic situation around the world is characterized by a tendency towards a slowdown of productivity, caused by, on the one hand, the digitalization of economic processes, and, on the other, by the consequences of COVID-19. This volume will be useful for researchers and PhD students, policymakers and economists, sociologists and philosophers, who are engaged in studying the interdisciplinary problems of the productivity of economies, an.